2011
DOI: 10.1162/coli_a_00072
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automatic Error Analysis of Machine Translation Output

Abstract: Evaluation and error analysis of machine translation output are important but difficult tasks. In this article, we propose a framework for automatic error analysis and classification based on the identification of actual erroneous words using the algorithms for computation of Word Error Rate (WER) and Position independent word Error Rate (PER) which is just a very first step towards development of automatic evaluation measures which provide more specific information of certain translation problems. The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…It implements the method based on the standard word error rate () combined with the precision and recall based error rates (Popović and Ney, 2007) and it has been tested on various language pairs and tasks. It is shown that the obtained results have high correlation (between 0.6 and 1.0) with the results obtained by human evaluators (Popović and Burchardt, 2011;Popović and Ney, 2011).…”
Section: Motivationsupporting
confidence: 54%
“…It implements the method based on the standard word error rate () combined with the precision and recall based error rates (Popović and Ney, 2007) and it has been tested on various language pairs and tasks. It is shown that the obtained results have high correlation (between 0.6 and 1.0) with the results obtained by human evaluators (Popović and Burchardt, 2011;Popović and Ney, 2011).…”
Section: Motivationsupporting
confidence: 54%
“…Furthermore, in Fishel et al (2012) a collection of annotated translation errors is presented, consisting of automatically produced translations and their detailed manual analysis. 14 Using the collected corpora, the authors evaluated two available state-of-the-art methods of MT diagnostics and assessment: Addicter (Zeman et al 2011) 15 and Hjerson (Popović and Ney 2011). 16 Addicter is an open-source tool that uses a method explicitly based on aligning the hypothesis and reference translations to devise the various error types.…”
Section: Related Workmentioning
confidence: 99%
“…So far, the relation between errors and automatic metrics has been analysed by measuring the correlation between single or total error frequencies and automatic scores (Popović and Ney, 2011;Farrús et al, 2012). Using two different error taxonomies, both works show that the sum of the errors has a high correlation with BLEU and TER scores.…”
Section: Related Workmentioning
confidence: 99%